(3eNGQL GdMQha hUaGJgGs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hMOg hHYO , adjS cd bGHd gOjI eMJGLG EdjgG , hGdGcd WGdH JMaI aGbOkG dgG C(B: (3ai SHH MOhK GdUhJ s
(3BNQgG (B:s
(3hef dZGJ Ce THjgI GddZGJ HfZe GdWjQ , hCXf Cfi bO HdZJ GdcaGjI hYHQJ Yf GdebOGQ GdPi Sdag eYQaJi aMGf Cf CNJe GdQSGdI MGeOkG Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3cJHJ HQSe fhM GHf jhSas
(3fSNI ajgG VHW Sgd GdfbW CMjGfkGs
(3fbd GdfGSN GdaUd GdQGHY hGdNGeS hGdSGOS HYO GfJgGA GdfU ef fSNI CNQi eNGdaI deG ai gPg GdfSNIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs